KARAKTERISTIK KOMUNITAS NEMATODA DI PADANG GOLF SUKARAME (PGS) BANDAR LAMPUNG - I Gede Swibawa dan Titik Nur Aeny . (Universitas Lampung, 2007)
ABSTRACTCharacteristic of Nematodes Community at PGS Golf Course Bandar Lampung. Golf course is a unique ecosystem where plant parasitic nematodes inhabit and become important pest because they reduce the quality of the grass. The pest problems on golf course can be indicated by its characteristics of nematode community. Survey on nematodes community at PGS Golf Course Bandar Lampung was conducted from March to December 2004. The objective was to study the characteristics of nematode community in the part of golf courses hole (green, collar, apron, and fairway). Soil samples were taken from five holes each of it consists of green, collar, apron, and fairway, respectiveley. Nematodes extraction was done in Laboratory of Arthropod Pest, Department of Plant Protection University of Lampung. The result showed that at least 50 nematodes genera of 28 families inhabit PGS. The number of plant parasitic nematode genera was higher than the free-living one. The characteristic of nematodes community on green and collar was different than on faiway. Nematode abundance and diversity on green and collar were higher than on fairway. Based on abundance of nematode feeding group, maturity index of free-living nematodes (MI) and that of plant parasitic nematodes (PPI), green and collar part seemed to be more favorable to plant parasitic nematodes than free-living nematodes. The contrary happened for fairway. Four most dominant genera of plant parasitic nematodes on PGS golf course were Helicotylenchus, Hoplolaimus, Criconemella, and Xiphinema.